Ефективність функціонування паливно-енергетичного комплексу України при переході в Європейську енергетичну систему - Поспєлов, О. В. (НТУ "ХПІ", 2014)
У статті розглянуті основні фактори, що впливають на розвиток та ефективне функціонування паливно-енергетичного комплексу України. Проаналізовані основні завдання та пріоритетні напрямки щодо змін та розвитку ПЕК України у розрізі вступу в європейську енергетичну систему. З наукових позицій оцінено та надано практичні рекомендації щодо оптимізації управління інноваційно-інвестиційним розвитком цієї базової галузі країни. Розроблені рекомендації щодо підвищення ефективності перетворення і використання енергії.

The topicality of the research is due to the fact that the most significant negative consequences of ill-conceived policies of the organization, management, planning and government regulation was reflected primarily in basic industries, which are industries of the fuel and energy complex. The article considers the main factors affecting the development and effective functioning of the fuel and energy complex of Ukraine. Analyzed the main challenges and priorities regarding change and development fuel and energy complex of Ukraine in the context of accession to the European energy system. Scientifically assessed and practical recommendations for improving management of innovation and investment development of this basic industry of the country. Developed recommendations for improving the efficiency of conversion and use of energy. The contradiction between the right course of transition to market type of regulation of the economy and not always consistent methods of its implementation – the main cause of current well-being, both in political and everyday life.
Efficiency of functioning of the fuel and energy complex of Ukraine during the transition of the European energy system
Keywords: енергетика; паливно-енергетичний комплекс; ПЕК; європейська інтеграція; енергетична система; power engineering; fuel and energy complex; European integration; energy system